ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMA PADA MATERI INTEGRAL - Kumala Dewi; Dori Lukman Hakim (Universitas Muhammadiyah Semarang, 2021)
In this research, the researcher wanted to analyze the students' mathematical understanding ability on integral material by using a descriptive qualitative approach. One of the class XII students of SMAN 1 Cikarang Barat was made the subject of this research. The instrument used in this research is a test instrument, which is in the form of an integral material description test question which consists of 7 questions. The results of problem solving by students will be analyzed based on indicators of mathematical understanding, namely interpreting, exemplifying (giving examples), classifying, summarizing, inferring, comparing, and explaining. The results showed that the research subjects were only able to answer 3 questions correctly, which means they were only able to fulfill 3 of the 7 indicators of mathematical understanding. Indicators of mathematical understanding that can be fulfilled by research subjects are summarizing, classifying, and exemplifying (giving examples).